Revision of Vajiralongkorn Dam’s Reservoir Characteristic Curves Using NDWI Derived from Landsat 8 Data - Yutthana Phankamolsil (2020)
Reservoir characteristics are the essential information for water management planning and reservoir operation. Regular monitoring and assessment of the reservoir characteristics can reduce risks associated with the reservoir operation. This research assessed the reservoir characteristics (water surface, volume) of Vajiralongkorn Dam using remote sensing. Reservoir water surface was classified using the Normalized Difference Water Index (NDWI) derived from the Landsat 8 data, and validated using the streamline matching rate (SMR) and the streamline matching error (SME) techniques for shoreline accuracy assessment. The volume between two water levels was calculated using the prismatic equation. The storage capacity curve was constructed from the reservoir water level and cumulative volume. The accuracy of NDWI technique was satisfactory in identifying reservoir water surface with a good accuracy of shoreline delineation (SMR>95% and SME=11.7 m). The water surface has decreased on the average of 8.2 km2 (2.8%) compared with the original data in 1980. The storage capacity has decreased 495.3 million m3 (MCM) over 38 years from 1980 to 2018, an annual capacity loss of 13 MCM. Finally, sustainable service of the reservoir needs better knowledge of the effects of storage loss, the erosion and sediment-transport processes, and conservation measures.